Lecturers’ perspectives on the level and factors that contribute to academic success in biomedical sciences among Ugandan nursing students: a descriptive qualitative study - Clement Munguiko; Anne Ngeno; Safinah Museene (BMC Medical Education)
Abstract Background Academic success in biomedical science courses is essential for nursing students to advance in clinical training and deliver quality care. However, many face challenges in these courses. This study explored lecturers’ perspectives on the academic success of Ugandan nursing students in biomedical sciences and the contributing factors. Methods A descriptive qualitative study was conducted across four public universities in Uganda, with purposively selected lecturers serving as participants. Data were collected through in-depth interviews guided by a structured interview guide. The data were analysed using inductive thematic approach and findings were presented narratively, supported by illustrative quotes. Findings Twelve lecturers participated in the study, nine themes and twenty-one subthemes emerged. Lecturers characterized the level of academic achievement as progressive, context-dependent, and marginal. Sociodemographic, individual educational, and institutional factors that influence academic success in biomedical sciences were revealed. Conclusion Degree nursing students continue to register marginal academic success in biomedical sciences which contributes negatively to their progress in the academic program and provision of quality patient care. Addressing sociodemographic, individual educational and institutional factors can enhance academic success in biomedical sciences, strengthen nursing education, improve patient care, contribute to socioeconomic development, and help mitigate the national, regional, and global shortage of nurses.